Genome-wide meta-analysis identifies a novel susceptibility signal at CACNA2D3 for nicotine dependence - Yin, Xianyong (Am J Med Genet B Neuropsychiatr Genet, 2017)
Nicotine dependence (ND) has a reported heritability of 40–70%. Low-coverage whole-genome sequencing was conducted in 1,889 samples from the UCSF Family study. Linear mixed models were used to conduct genome-wide association tests of ND in this and five cohorts obtained from the database of Genotypes and Phenotypes. Fixed-effect meta-analysis was carried out separately for European (n = 14,713) and African (n = 3,369) participants, and then in a combined analysis of both ancestral groups. The meta-analysis of African participants identified a significant and novel susceptibility signal (rs56247223; P = 4.11 × 10(−8)). Data from the Genotype-Tissue Expression (GTEx) study suggested the protective allele is associated with reduced mRNA expression of CACNA2D3 in three human brain tissues (P < 4.94 × 10(−2)). Sequence data from the UCSF Family study suggested that a rare nonsynonymous variant in this gene conferred increased risk for ND (P = 0.01) providing further support for CACNA2D3 involvement in ND. Suggestive associations were observed in six additional regions in both European and merged populations (P < 5.00 × 10(−6)). The top variants were found to regulate mRNA expression levels of genes in human brains using GTEx data (P < 0.05): HAX1 and CHRNB2 (rs1760803), ADAMTSL1 (rs17198023), PEX2 (rs12680810), GLIS3 (rs12348139), non-coding RNA for LINC00476 (rs10759883), and GABBR1 (rs56020557 and rs62392942). A gene-based association test further supported the relation between GABBR1 and ND (P = 6.36 × 10(−7)). These findings will inform the biological mechanisms and development of therapeutic targets for ND.